The Influence Of Leadership, Communication And Motivation On Employee Performance At PT. Tjipta Rimba Djaja - Elvina Zerlinna; Yudha Pratama; Gian Ginarha Citra; Leni Faroka; Hendry (Institute of Computer Science (IOCS), 2021)
This study aims to determine the effect of leadership, communication, and motivation on employee performance at PT. Tjipta Rimba Djaja. This type of research is explanatory research. The population in this study were all employees who work at PT. Tjipta Rimba Djaja, totaling 205 people. Due to the large number of population, the sampling technique will be reduced by using the Slovin formula with an error tolerance level of 5% so that there are 136 respondents. In the study which will be distributed with questionnaires measured by a Likert scale. The data analysis used multiple linear regression analysis and the coefficient of determination as well as simultaneous test and partial test. The results showed that leadership, communication, and motivation partially or simultaneously have a positive and significant effect on employee performance at PT. TjiptaRimbaDjaja. Based on the results of this study, the implications for management are to further improve leadership, improve a better communication, imporve the motivation.